Withaferin A induces cell death and differentiation in multiple myeloma cancer stem cells. Issue 1 (24th November 2016) - Issa, Mark E.; Cuendet, Muriel
Abstract : Withaferin A induced the differentiation of multiple myeloma cancer stem cells in vitro, and altered the expression of stemness and differentiation markers. Abstract : Multiple myeloma (MM) remains an incurable malignancy despite the development of novel therapeutics. This is believed to be due to a subset of rare chemotherapy-resistant cancer stem cells (CSCs). Differentiation therapy represents one strategy aimed at reducing the stemness of CSCs. The anticancer effect of withaferin A (WFA) was studied in MM-CSCs and RPMI 8226 MM tumoral plasma cells (RPMIs). WFA exhibited growth inhibitory effects in both MM-CSCs and RPMIs, with IC50 values of 649 and 224 nM, respectively. WFA also induced a G2 cell cycle arrest, as well as cell death and apoptosis. Although, WFA did not exhibit a direct anti-migratory effect, a remarkable morphological change was observed in MM-CSCs in response to WFA treatment. Using qPCR gene expression analyses, WFA caused a reduction in stemness markers, and a promotion of differentiation markers in MM-CSCs. These results warrant further investigation of WFA in relevant MM animal models.